RI 3193 Character of Drainage from Mines in the Thick Freeport Coal Bed, Pennsylvania - R. D. Lieitch; P. Yant; R. R. Sayers (The National Institute for Occupational Safety and Health (NIOSH), 1932)
"PURPOSE OF INVESTIGATIONOf more than 300 bituminous mines examined by Crichton 5 and his assistants in connection with litigation in Indian Creek Valley, Payette County, Pa., only four were found to have alkaline water. That work and many observations from of the authors have shown the general prevalence or acid drainage from bituminous coal mines. In connection with investigations pertinent to coal-mine drainage that are being conducted by the United States Bureau of Mines, it was noted with considerable interest therefore, that a mine in the Thick Freeport bed about 20 miles north of Pittsburgh had no acid water in the workings, As it was thought that this condition might be common to all mines,this condition in this bed most of them were visited, samples of the outflow and from different parts of the mine inside were examined, and such general information as was available was gathered.ACKNOWLEDGMENTSThe authors acknowledge with thanks the courteous assistance of mine officials in connection with collecting the data for this paper, and of the analytical and coal laboratories of the Bureau of Mines for analyses."